2018
DOI: 10.1096/fj.201800448r
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload by transferrin receptor protein 1 regulation plays an important role in palmitate‐induced insulin resistance in human skeletal muscle cells

Abstract: Free fatty acid is considered to be one of the major pathogenic factors of inducing insulin resistance. The association between iron disturbances and insulin resistance has recently begun to receive a lot of attention. Although skeletal muscles are a major tissue for iron utilization and storage, the role of iron in palmitate (PA)-induced insulin resistance is unknown. We investigated the molecular mechanism underlying iron dysregulation in PA-induced insulin resistance. Interestingly, we found that PA simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 58 publications
(71 reference statements)
0
24
0
Order By: Relevance
“…In our study, the concentrations of Zn, Cu, and Fe in maternal serum in the 10-14th week were not associated with LGA risk, although these microelements are also associated with metabolic disorders, such as insulin resistance as well as diabetes mellitus and obesity [16][17][18]. In their optimal levels, they also have antioxidant and anti-inflammatory properties, and their deficiency or excess may increase inflammation and oxidative stress [15].…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…In our study, the concentrations of Zn, Cu, and Fe in maternal serum in the 10-14th week were not associated with LGA risk, although these microelements are also associated with metabolic disorders, such as insulin resistance as well as diabetes mellitus and obesity [16][17][18]. In their optimal levels, they also have antioxidant and anti-inflammatory properties, and their deficiency or excess may increase inflammation and oxidative stress [15].…”
Section: Discussionmentioning
confidence: 46%
“…Microelements such as selenium (Se), zinc (Zn), copper (Cu), and iron (Fe) have anti-inflammatory and antioxidant properties, and their deficiency or excess can increase inflammation and oxidative stress [14,15]. These microelements are involved in insulin signal cascade regulation, glucose metabolism, and the functions of many hormones [11,[16][17][18]. They also affect cell proliferation and differentiation [2,14,19].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas iron deficiency leads to anaemia (Zimmermann & Hurrell, 2007), high body iron stores have been associated with metabolic dysfunction and the development of type 2 diabetes (Jehn, Clark, & Guallar, 2004; Jiang et al., 2004). The mechanisms linking iron and metabolic dysfunction are incompletely understood (Fernández‐Real, McClain, & Manco, 2015), but some pre‐clinical evidence indicates that excess muscle iron impairs peripheral insulin signalling (Cui et al., 2019). Although whole‐body iron stores vary markedly among adults with obesity (Aigner et al., 2014), it was reported that markers of iron content in skeletal muscle correlated with BMI, suggestive of increased muscle iron storage in obesity (Moreno‐Navarrete et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Zhang et al (20) reported that calcium channel blockers (CCBs) ameliorated iron overload-associated hepatic fibrosis by altering iron transport, and indicated that ccBs are potential therapeutic agents for iron overload-induced diseases. calcium was reported to modulate receptor-mediated endocytosis and, as TfR1 modulates iron influx through this pathway, it was further demonstrated that calcium could antagonize iron-TF-TfR1 complex internalization and, thus, modulate iron uptake (21).…”
Section: Calcium Chelator Bapta-am Protects Against Iron Overload-induced Chondrocyte Mitochondrial Dysfunction and Cartilage Degeneratiomentioning
confidence: 97%